2000
DOI: 10.1046/j.1365-2273.2000.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised clinical trial of turbinectomy for compensatory turbinate hypertrophy in patients with anterior septal deviations

Abstract: Turbinectomy is performed at the time of nasal septal surgery by many otolaryngologists. One reason given for this procedure is the presence of a hypertrophied contralateral inferior turbinate. A randomised trial was undertaken to evaluate the relief of nasal obstruction following contralateral turbinectomy with septal surgery. Patients presenting with nasal obstruction who had a unilateral septal deviation and contralateral inferior turbinate enlargement were prospectively randomized to contralateral turbinec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 15 publications
1
31
0
1
Order By: Relevance
“…In patients one would frequently fi nd crustations at this point. In middle and posterior deviations of the nose This change in form of the lateral nasal wall is known as compensatory turbinate hypertrophy [2][3][4][5] . In models F-H, J-L and N-P, turbinates of differing sizes were introduced to compensate for the dead space caused by septal deviation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients one would frequently fi nd crustations at this point. In middle and posterior deviations of the nose This change in form of the lateral nasal wall is known as compensatory turbinate hypertrophy [2][3][4][5] . In models F-H, J-L and N-P, turbinates of differing sizes were introduced to compensate for the dead space caused by septal deviation.…”
Section: Discussionmentioning
confidence: 99%
“…This compensatory mechanism has been greatly documented in the medical literature [2][3][4][5] . However, a specifi c investigation of turbinate adaptation for the airfl ow dynamics in noses with septal deviation has not yet been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…The turbinate procedures include subtotal or total turbinectomy, mucosal cautery, submucous resection, and turbinate fracture. [12][13][14][15][16][17][18][19] In a large series, Rohrich et al 12 advocate submucous resection as an important adjunct to rhinoplasty. Mabry 13 popularized a partial turbinectomy technique, but recommended that the surgeon perform the most conservative surgical approach to the turbinates that consistently provides a good airway in that surgeon's hands.…”
Section: Discussionmentioning
confidence: 99%
“…Objectives B and C: understanding experiences of septoplasty and non-surgical management We will investigate patients' (n = [16][17][18][19][20] and health professionals' (n = [16][17][18][19][20] experiences of the interventions and trial participation through qualitative interviews conducted during patient follow-up. Where possible, patients for the follow-up interviews will include those interviewed during the recruitment phase; additional participants will be recruited based on purposive and emergent criteria (e.g.…”
Section: Sampling Strategymentioning
confidence: 99%
“…There is also a lack of robust evidence about the additional benefit of turbinate surgery [11]. One study showed reduced revision rates for septoplasty when the turbinate tissue is reduced [15]; other studies report no added long-term benefit from turbinate reduction [16][17][18].…”
mentioning
confidence: 99%